PENGARUH TRANSFER PRICING, THIN CAPITALIZATION,DAN TUNNELING INCENTIVE TERHADAP AGRESIVITAS PAJAK - Muthia Athira Hutomo, (2021)
This research is using quantitative study aimed to see whether there are influence of transfer pricing, thin capitalization, and tunneling incentive on tax aggressiveness. This study uses manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The sample used is 530 samples. Transfer Pricing is measured based on the comparison of receivables from related parties with total assets. Thin Capitalization is measured using the MAD Ratio. Tunneling Incentive is measured using a dummy variable. Tax aggressiveness is measured using ABTD. The analytical method for this study uses descriptive analysis and multiple linear analysis hypothesis testing with the help of SPSS 26. The results of this study indicate that Transfer Pricing, Thin Capitalization and Tunneling Incentives have no effect on Tax Aggressiveness.